PENGARUH PRODUK, PELAYANAN, HARGA DAN LOKASI - Sofianti Sofianti (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2022)
Hotel is one of commercial accommodation, it’s provide services rooms, foods and beverages for need customers. The competitors is one of hotel owner can be see any other plus facilities to provide customer. The hotel wants to give added value is difference product and service to customer. It’s to do owner hotel because reality that customer not satisfaction product and service, than customer look for other hotel to be customer satisfaction. JW Marriott hotel Surabaya is one five star hotel to give product and quality service excellence to customer. The price is to give JW Marriot hotel Surabaya suitable product and service customer. JW Marriott hotel Surabaya to give special rate promotion and member facilities to customer and repeater guest hotel too. JW Marriott hotel have strategic location because there are centre of city to business, shopping centre, office centre and transportation. The expected outcome of this research is the known of the factors variable product, service, price, and location that affect customer satisfaction on JW Marriot hotel is simultan and parcial.